Ein feministischer Blick auf Wasser: Das Beispiel Indien - Aithal, Vathsala (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1997)
Water is a structural element of Indian society. Colonial interventions not only destroyed the ecosystems but also disappropriated the rights of the people to use and control the commons. With no changes in the post-colonial period women in their productive and reproductive mies are the most affected by the consequences of waterscarcity and drought. Many development projects not only failed to address the longterm strategic gender needs but also failed to meet even the practical need of providing water. Initiatives of women’s groups however do combine their struggle for water with issues of equity and gender justice.